A solid electrolyte and its preparation method and application

Through high-voltage and high-temperature synthesis technology, a solid electrolyte with the general chemical formula of LixByOzSw was prepared, which solved the problem that the existing electrolytes could not have both high conductivity, voltage stability and chemical stability, and achieved excellent performance in all-solid-state batteries.

CN114784369BActive Publication Date: 2025-02-25SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210479530.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-05
Publication Date
2025-02-25
Estimated Expiration
2042-05-05

AI Technical Summary

Technical Problem

The existing solid-state electrolytes cannot have both high conductivity, voltage stability and high chemical stability, which limits their application in all-solid-state batteries.

Method used

By synthesizing the formed raw materials under high pressure (0.1-30GPa) and high temperature (500-3000℃), a solid electrolyte with the general chemical formula of LixByOzSw was prepared, which improved its crystallinity and chemical stability.

Benefits of technology

It realizes the high conductivity, voltage stability and chemical stability of solid electrolytes, and has good application prospects in all solid state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114784369B_ABST
    Figure CN114784369B_ABST
Patent Text Reader

Abstract

The present application relates to the field of lithium-ion battery technology, and more specifically, to a solid electrolyte and its preparation method and application. The preparation method of the solid electrolyte comprises synthesizing formed raw materials; the synthesis pressure is 0.1-30GPa, the synthesis temperature is 500-3000℃; the chemical formula of the solid electrolyte is Li x B y O z S w , where 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a solid electrolyte and a preparation method and application thereof. Background Art

[0002] Solid-state electrolytes are mainly divided into two categories: oxide type and sulfide type, including perovskite type, NASICON type, LISICON type, garnet type and Li3N type.

[0003] Oxide-based solid electrolytes are mainly represented by La 2 / 3-x Li3 x TiO3、Li 1+x Al x Ti 2-x (PO4), Li7La3Zr2O 12 、Li4B7O 12 C l , Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 14 ZnGe4O 16 Or LiPON, etc. The main advantages of oxide-type solid electrolytes are good structural stability and good safety. However, oxide-type solid electrolytes have low electrical conductivity, poor sintering performance and high raw material cost, which greatly limits the application of oxide-type solid electrolytes.

[0004] Including Li 10 GeP2S 12 The main advantages of sulfide-type solid electrolytes (LGPS) are good mechanical ductility, excellent interface contact performance and high electrical conductivity. However, sulfide-type solid electrolytes have poor stability to lithium metal and low safety. In addition, the preparation process has high requirements for environmental moisture and is easy to absorb moisture and release toxic gas H2S, causing environmental pollution and safety problems.

[0005] The existing solid-state electrolytes are limited in types and cannot simultaneously combine the advantages of high conductivity, voltage stability, and high chemical stability. In addition, there are currently great technical difficulties in modifying solid-state electrolytes, which greatly limits the application of solid-state electrolytes in all-solid-state batteries. Summary of the invention

[0006] The purpose of the present application is to provide a solid electrolyte and a preparation method and application thereof, which is intended to solve the technical problem that existing solid electrolytes cannot simultaneously have high electrical conductivity, voltage stability and high chemical stability.

[0007] The first aspect of the present application provides a method for preparing a solid electrolyte, comprising: synthesizing the formed raw materials; the pressure for synthesis is 0.1 - 30 GPa, and the temperature for synthesis is 500 - 3000 °C; the general chemical formula of the solid electrolyte is Li x B y O z S w , where 0 < x ≤ 4, 0 < y ≤ 7, 0 < z ≤ 11, 0 < w ≤ 2.

[0008] In the present application, by synthesizing the formed raw materials to prepare a solid electrolyte with the general chemical formula of Li x B y O z S w (where 0 < x ≤ 4, 0 < y ≤ 7, 0 < z ≤ 11, 0 < w ≤ 2), with the synthesis pressure being 0.1 - 30 GPa and the synthesis temperature being 500 - 3000 °C, the utilization rate of raw materials and the rate of the synthesis reaction can be improved, and the prepared solid electrolyte has good crystallization, a complete crystal structure without defects, and extremely few by-products, which is beneficial to improving the conductivity, voltage stability, and chemical stability of the solid electrolyte and has good application prospects in all-solid-state batteries.

[0009] In some embodiments of the first aspect of the present application, the pressure for the above synthesis is 3 - 5 GPa, and the temperature for the synthesis is 800 - 1000 °C.

[0010] In some embodiments of the first aspect of the present application, the time for the above synthesis is 1 - 100 min.

[0011] In some embodiments of the first aspect of the present application, before synthesizing the formed raw materials, ball milling and mixing the raw materials are further included; the ball-to-material ratio for ball milling and mixing is (5 - 20):1, and the rotation speed for ball milling and mixing is 100 - 500 r / min.

[0012] In some embodiments of the first aspect of the present application, the time for the above ball milling and mixing is 3 - 10 h.

[0013] In some embodiments of the first aspect of the present application, the preparation steps of the above formed raw materials include: pre-pressing the raw materials at 1 - 30 MPa for 1 - 20 min.

[0014] In some embodiments of the first aspect of the present application, the above raw materials include a lithium source, a boron source, a sulfur source, and an oxygen source; the lithium source includes at least one of lithium oxide and lithium sulfide, the boron source includes at least one of boron powder, boron oxide, and boron sulfide, the sulfur source includes at least one of sulfur powder, lithium sulfide, and boron sulfide, and the oxygen source includes at least one of lithium oxide and boron oxide.

[0015] In some embodiments of the first aspect of the present application, the above-mentioned synthetic device is selected from any one of a two-sided press, a four-sided press and a hinged six-sided press.

[0016] A second aspect of the present application provides a solid electrolyte, which is prepared by the solid electrolyte preparation method provided by the first aspect.

[0017] The solid electrolyte prepared by the preparation method of the solid electrolyte provided in the first aspect of the present application can have high electrical conductivity, voltage stability and chemical stability, and has good application prospects in all-solid-state batteries.

[0018] The third aspect of the present application provides an application of the solid electrolyte provided in the second aspect in the preparation of an all-solid-state battery.

[0019] Applying the solid electrolyte provided in the present application to an all-solid-state battery can improve the conductivity, voltage stability and chemical stability of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 A schematic structural diagram of the sample assembly used for high pressure synthesis provided in the present application is shown.

[0022] Figure 2 The conductivity test diagram of the solid electrolyte prepared in Example 1 of the present application at different temperatures is shown.

[0023] Figure 3 The electrochemical window test diagram of the solid electrolyte prepared in Example 1 of the present application is shown.

[0024] Figure 4 The XRD patterns of the solid electrolyte prepared in Example 1 of the present application after being exposed to air for 0 h and 7 days are shown.

[0025] Figure 5 The charge and discharge performance diagram of a battery assembled using the solid electrolyte prepared in Example 1 of the present application is shown.

[0026] Figure 6 The conductivity test diagram of the solid electrolyte prepared in Comparative Example 1 of the present application at different temperatures is shown.

[0027] Icon: 110 - first placement tube; 111 - first sample chamber; 120 - first sealing sheet; 130 - second placement tube; 140 - second sealing sheet; 150 - third placement tube; 160 - third sealing sheet; 170 - first metal sheet; 180 - conductive steel ring; 190 - fourth placement tube. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0029] The following is a detailed description of a solid electrolyte and its preparation method and application provided in an embodiment of the present application.

[0030] The present application provides a method for preparing a solid electrolyte, comprising synthesizing a formed raw material; the synthesis pressure is 0.1-30GPa, and the synthesis temperature is 500-3000°C. The chemical formula of the solid electrolyte is Li x B y O z S w , where 0 <x≤4,0<y≤7,0<z≤11,0<w≤2。

[0031] The present application prepares synthetic lithium boron sulfide compounds by selecting atoms in a solid electrolyte and regulating the atomic ratio; when the selection of atoms and the atomic ratio in the solid electrolyte conform to the general chemical formula of the above-mentioned solid electrolyte, it provides an atomic basis for the solid electrolyte to have a better crystal structure, and is also beneficial to significantly improve the electrical conductivity, voltage stability and chemical stability of the solid electrolyte.

[0032] As an example, in the general chemical formula of the solid electrolyte, the value of x can be 1, 2, 3 or 4, etc.; the value of y can be 1, 2, 3, 4, 5, 6 or 7, etc.; the value of z can be 5, 6, 7, 8, 9, 10 or 11, etc.; the value of w can be 1 or 2.

[0033] As an example, the solid electrolyte may be Li4B6O9S2, LiB7O8S, Li3B6O 11 S or LiB6O 10 S et al.

[0034] The synthesis pressure is 0.1-30GPa and the synthesis temperature is 500-3000°C. The above synthesis conditions can make the atoms of the formed raw materials collide with each other and then form a chemical formula of Lix B y O z S w Lithium borosulfate oxide compound (where 0 < x ≤ 4, 0 < y ≤ 7, 0 < z ≤ 11, 0 < w ≤ 2).

[0035] In addition, the above synthesis conditions are also beneficial to improving the crystallinity of the prepared solid electrolyte, enabling each atom in the solid electrolyte to individually occupy a site in the crystal lattice, forming a crystal structure with a cubic phase. The cubic phase structure has a high symmetry of atomic arrangement, high isotropy, and a complete and defect-free crystal structure, which is beneficial to the rapid transmission of lithium ions. Furthermore, it is conducive to improving the conductivity, voltage stability (not easily decomposed under a voltage of 0 - 6V), and chemical stability (including stability towards lithium metal, sintering performance, air stability, and structural stability in the presence of water) of the solid electrolyte, and is expected to be applied in all-solid-state batteries. At the same time, the above synthesis conditions also improve the utilization rate of raw materials to reduce by-products during the preparation of the solid electrolyte and increase the reaction rate of the synthesis to reduce the time required for synthesizing the lithium borosulfate oxide compound, which is beneficial to large-scale industrial production.

[0036] Exemplarily, the synthesis pressure can be 0.1 GPa, 0.5 GPa, 5 GPa, 10 GPa, 15 GPa, or 30 GPa, etc.; the synthesis temperature can be 500 °C, 700 °C, 1000 °C, 1500 °C, 2000 °C, or 3000 °C, etc.

[0037] Furthermore, when the synthesis pressure is 3 - 5 GPa and the synthesis temperature is 800 - 1000 °C, the above synthesis conditions can further improve the crystallization performance, conductivity, voltage stability, and chemical stability of the solid electrolyte.

[0038] In this application, the synthesis time is 1 - 100 min. Exemplarily, the synthesis time can be 1 min, 5 min, 20 min, 50 min, or 100 min, etc.

[0039] In this application, the raw materials include a lithium source, a boron source, a sulfur source, and an oxygen source; the lithium source includes at least one of lithium oxide, lithium peroxide, and lithium sulfide, the boron source includes at least one of boron powder, boron oxide, and boron sulfide, the sulfur source includes at least one of sulfur powder, lithium sulfide, and boron sulfide, and the oxygen source includes at least one of lithium oxide and boron oxide.

[0040] It should be noted that lithium oxide and lithium peroxide can be used as both the oxygen source and the lithium source, lithium sulfide can be used as both the sulfur source and the lithium source, boron oxide can be used as both the oxygen source and the boron source, and boron sulfide can be used as both the sulfur source and the boron source, as long as the raw materials can satisfy the general chemical formula of the above solid electrolyte.

[0041] It should be further explained that, in other embodiments of the present application, the raw materials are not limited to the above-mentioned substances, as long as the raw materials can satisfy the general chemical formula of the above-mentioned solid electrolyte.

[0042] In the present application, the raw materials are ball-milled before being synthesized. Ball-milling can improve the uniformity of the mixing between the raw materials, which is conducive to making the synthesis easier and increasing the synthesis rate in the subsequent synthesis process, and is conducive to improving the crystallinity of the prepared solid electrolyte.

[0043] Furthermore, the ball-to-material ratio of ball milling is (5-20):1, and the rotation speed of ball milling is 100-500r / min, which is beneficial to further improve the uniformity of mixing between the raw materials and make the particle size of the raw materials smaller, which is beneficial to make the synthesis in the subsequent synthesis process easier, increase the synthesis rate and improve the raw material utilization rate of the subsequent synthesis reaction, and also help to improve the crystallinity of the prepared solid electrolyte.

[0044] As an example, the ball-to-material ratio of ball milling can be 5:1, 8:1, 10:1, 12:1, 15:1 or 20:1, etc., and the rotation speed of ball milling can be 100r / min, 120r / min, 200r / min, 230r / min, 300r / min or 500r / min, etc.

[0045] Furthermore, the ball milling mixing time is 3-10 hours, which is beneficial to improve the uniformity of mixing between the raw materials and the crystallinity of the prepared solid electrolyte. As an example, the ball milling mixing time can be 3 hours, 4 hours, 6 hours, 7.5 hours, 8 hours or 10 hours, etc.

[0046] It should be noted that the present application does not limit the particle sizes of the raw materials and the grinding bodies in the ball milling mixing.

[0047] In the present application, the preparation steps of the formed raw materials include: pre-pressing the raw materials at 1-30 MPa for 1-20 min. The above conditions can make the raw materials have a certain shape, which is convenient for subsequent synthesis; at the same time, the above pre-pressing conditions can make the gaps between the raw materials tighter, which is more conducive to the collision between atoms in the raw materials during the high-pressure synthesis process, and is beneficial to improving the crystallinity of the prepared solid electrolyte.

[0048] As an example, the pre-pressing pressure in the preparation step of the formed raw material can be 1MPa, 5MPa, 10MPa, 20MPa or 30MPa, etc., and the pre-pressing time can be 1min, 5min, 8min, 10min, 15min or 20min, etc.

[0049] In the present application, the synthesis device can be selected from any one of a two-sided top press, a four-sided top press, and a hinged six-sided top press. It should be noted that in other embodiments of the present application, the synthesis device can also be selected from other high-pressure synthesis devices, as long as the synthesis pressure can be 0.1-30GPa and the synthesis temperature can be 500-3000°C.

[0050] Figure 1 The schematic diagram of the structure of the sample assembly used for high pressure synthesis provided in this application is shown in Figure 1 In this embodiment of the present application, the step of placing the formed raw material in the synthesis device includes: placing the formed raw material in the first sample cavity 111 of the first placement tube 110, and then sealing the upper and lower ends of the first placement tube 110 with the first sealing sheet 120; placing the sealed first placement tube 110 in the second placement tube 130, and then sealing the upper and lower ends of the second placement tube 130 with the second sealing sheet 140; placing the second placement tube 130 in the third placement tube 150, and then sealing the upper and lower ends of the third placement tube 150 with the third sealing sheet 160; then successively setting the first metal sheet 170 and the conductive steel ring 180 on the side of the third sealing sheet 160 on both sides of the third placement tube 150 away from the second placement tube 130 to obtain an intermediate assembly; finally, placing the intermediate assembly in the fourth placement tube 190. Among them, the material of the first placement tube 110 and the first sealing sheet 120 are independently selected from any one of boron nitride, sodium chloride and magnesium oxide; the material of the second placement tube 130, the second sealing sheet 140 and the third sealing sheet 160 are selected from graphite; the material of the third placement tube 150 is selected from any one of dolomite or talc; the material of the first metal sheet 170 is selected from molybdenum; the material of the fourth placement tube 190 is selected from talc.

[0051] The function of the first placement tube 110 and the first sealing sheet 120 is to isolate the sample from the external environment and to keep it warm; the function of the second placement tube 130, the second sealing sheet 140 and the third sealing sheet 160 is to heat the sample and provide the temperature required for synthesis; the function of the third sealing tube 150 is to keep it warm to ensure the temperature required for synthesis; the function of the first metal sheet 170 and the conductive steel ring 180 is to provide connectivity and conductivity; the function of the fourth placement tube 190 is to act as a pressure transmission medium to provide a relatively hydrostatic pressure environment, which is conducive to the synthesis device to better press the raw materials.

[0052] The preparation method of the solid electrolyte provided in this application has at least the following advantages:

[0053] The preparation method of the solid electrolyte provided in the present application is simple and easy, which is beneficial to improving the utilization rate of raw materials and the rate of synthesis reaction. The prepared solid electrolyte has good crystallization, a complete crystal structure without defects, and very few by-products, which is beneficial to improving the conductivity, voltage stability and chemical stability of the solid electrolyte. It is easy to industrialize large-scale production and has good application prospects in all-solid-state batteries.

[0054] The present application also provides a solid electrolyte, which is prepared using the above-mentioned method for preparing the solid electrolyte.

[0055] The solid electrolyte provided in the present application can have high electrical conductivity, voltage stability and chemical stability, and has good application prospects in all-solid-state batteries.

[0056] The present application also provides an application of the solid-state electrolyte provided above in the preparation of an all-solid-state battery.

[0057] Applying the solid electrolyte provided in the present application to an all-solid-state battery can improve the conductivity, voltage stability and chemical stability of the all-solid-state battery.

[0058] The characteristics and performance of the solid electrolyte and the preparation method thereof of the present application are further described in detail below in conjunction with the embodiments.

[0059] Example 1

[0060] This embodiment provides a solid electrolyte and a preparation method thereof. The solid electrolyte is prepared using the following steps: the chemical formula of the solid electrolyte is Li4B6O9S2.

[0061] (1) Preparation of raw materials:

[0062] 5.22 g of boron oxide and 2.30 g of lithium sulfide were ball-milled and mixed; wherein the ball-to-material ratio was 10:1, the ball milling speed was 200 r / min, and the ball milling time was 6 h, to obtain a precursor powder;

[0063] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 15 MPa for 10 min to obtain a precursor blank.

[0064] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 4 GPa and 900°C for 10 min.

[0065] Example 2

[0066] This embodiment provides a solid electrolyte and a preparation method thereof. The solid electrolyte is prepared using the following steps: the chemical formula of the solid electrolyte is Li4B6O9S2.

[0067] (1) Preparation of raw materials:

[0068] 5.22 g of boron oxide and 2.30 g of lithium sulfide were ball-milled and mixed; wherein the ball-to-material ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h, to obtain a precursor powder;

[0069] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 1 MPa for 20 min to obtain a precursor blank.

[0070] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 0.1 GPa and 3000° C. for 100 min.

[0071] Example 3

[0072] This embodiment provides a solid electrolyte and a preparation method thereof. The solid electrolyte is prepared using the following steps: the chemical formula of the solid electrolyte is Li4B6O9S2.

[0073] (1) Preparation of raw materials:

[0074] 5.22 g of boron oxide and 2.30 g of lithium sulfide were ball-milled and mixed; wherein the ball-to-material ratio was 20:1, the ball milling speed was 100 r / min, and the ball milling time was 3 h, to obtain a precursor powder;

[0075] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 30 MPa for 1 min to obtain a precursor blank.

[0076] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 30 GPa and 500°C for 1 min.

[0077] Example 4

[0078] This embodiment provides a solid electrolyte and a preparation method thereof, wherein the solid electrolyte is prepared by the following steps: the chemical formula of the solid electrolyte is LiB7O8S;

[0079] (1) Preparation of raw materials:

[0080] 8.7 g of boron oxide, 1.08 g of boron powder, 0.75 g of lithium oxide and 1.6 g of sulfur powder were ball-milled and mixed; wherein the ball-to-material ratio was 10:1, the ball milling speed was 200 r / min, and the ball milling time was 6 h, to obtain a precursor powder;

[0081] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 15 MPa for 10 min to obtain a precursor blank.

[0082] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 4 GPa and 900°C for 10 min.

[0083] Example 5

[0084] This embodiment provides a solid electrolyte and a preparation method thereof. The solid electrolyte is prepared by the following steps: the chemical formula of the solid electrolyte is Li3B6O 11 S.

[0085] (1) Preparation of raw materials:

[0086] 2.09 g of boron oxide, 0.46 g of lithium peroxide, 0.23 g of lithium sulfide and 0.16 g of sulfur powder were ball-milled and mixed; wherein the ball-to-material ratio was 10:1, the ball milling speed was 200 r / min, and the ball milling time was 6 h, to obtain a precursor powder;

[0087] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 15 MPa for 10 min to obtain a precursor blank.

[0088] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 4 GPa and 900°C for 10 min.

[0089] Example 6

[0090] This embodiment provides a solid electrolyte and a preparation method thereof. The solid electrolyte is prepared by the following steps: the chemical formula of the solid electrolyte is LiB6O 10 S.

[0091] (1) Preparation of raw materials:

[0092] 2.09 g of boron oxide, 0.15 g of lithium oxide and 0.32 g of sulfur powder were ball-milled and mixed; wherein the ball-to-material ratio was 10:1, the ball milling speed was 200 r / min, and the ball milling time was 6 h, to obtain a precursor powder;

[0093] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 15 MPa for 10 min to obtain a precursor blank.

[0094] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 4 GPa and 900°C for 10 min.

[0095] Comparative Example 1

[0096] This comparative example provides a solid electrolyte and a preparation method thereof. The solid electrolyte is prepared by the following steps: the chemical formula of the solid electrolyte is Li4OBr2.

[0097] (1) Preparation of raw materials:

[0098] 1.74 g of lithium bromide and 0.3 g of lithium oxide were ball-milled and mixed; wherein the ball-to-material ratio was 10:1, the ball milling speed was 200 r / min, and the ball milling time was 6 h, to obtain a precursor powder;

[0099] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 15 MPa for 10 min to obtain a precursor blank.

[0100] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 4 GPa and 900°C for 10 min.

[0101] Comparative Example 2

[0102] This comparative example provides a solid electrolyte and a preparation method thereof. The solid electrolyte is prepared by the following steps: the chemical formula of the solid electrolyte is Li4B6O9S2.

[0103] (1) Preparation of raw materials:

[0104] 5.22 g of boron oxide and 2.30 g of lithium sulfide were ball-milled and mixed; wherein the ball-to-material ratio was 10:1, the ball milling speed was 200 r / min, and the ball milling time was 6 h, to obtain a precursor powder;

[0105] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 15 MPa for 10 min to obtain a precursor blank.

[0106] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 20 MPa and 900° C. for 10 min.

[0107] Comparative Example 3

[0108] This comparative example provides a solid electrolyte and a preparation method thereof. The solid electrolyte is prepared by the following steps: the chemical formula of the solid electrolyte is Li4B6O9S2.

[0109] (1) Preparation of raw materials:

[0110] 5.22 g of boron oxide and 2.30 g of lithium sulfide were ball-milled and mixed; wherein the ball-to-material ratio was 10:1, the ball milling speed was 200 r / min, and the ball milling time was 6 h, to obtain a precursor powder;

[0111] (2) Pre-pressing: The precursor powder obtained in step (1) is pre-pressed at 15 MPa for 10 min to obtain a precursor blank.

[0112] (3) High-pressure synthesis: The precursor blank obtained in step (2) was synthesized at 4 GPa and 200°C for 10 min.

[0113] Experimental Example 1

[0114] The Li4B6O9S2 solid electrolyte prepared in Example 1 was subjected to conductivity tests at different temperatures and electrochemical window tests. The conductivity results are as follows: Figure 2 As shown, the electrochemical window test results are as follows Figure 3 As shown; and the Li4B6O9S2 solid electrolyte prepared in Example 1 was exposed to air for 0h and 7 days after XRD characterization, the characterization results are as follows Figure 4 The Li4B6O9S2 solid electrolyte prepared in Example 1 was assembled into a battery with a configuration of LiFePO4||Li4B6O9S2||Li, and the charge and discharge performance of the battery was tested. The charge and discharge performance results are shown in Figure 5 As shown; wherein, the battery is prepared by the following steps: the solid electrolyte is pressed into an electrolyte sheet with a diameter of 10 mm, a metal lithium sheet with a diameter of 10 mm is attached to one side of the solid electrolyte sheet, and then a LiFePO4 electrode sheet with the same diameter is attached to the other side of the solid electrolyte sheet to form a sandwich structure, and finally assembled into a CR2035 button battery. The conductivity of the Li4OBr2 solid electrolyte prepared in Comparative Example 1 is tested at different temperatures, and the conductivity results are shown in Figure 6 shown.

[0115] Result analysis: From Figure 2-5 It can be seen that the Li4B6O9S2 solid electrolyte prepared in Example 1 of the present application has excellent conductivity, a wide electrochemical window, good air stability and good charge and discharge performance. Figure 2 and Figure 6 From the comparison, it can be seen that the Li4B6O9S2 solid electrolyte prepared in Example 1 has significantly higher conductivity than the Li4OBr2 solid electrolyte prepared in Comparative Example 1. This is because the Li4B6O9S2 solid electrolyte has Li-S bonds, which makes it easier for lithium ions to migrate.

[0116] Experimental Example 2

[0117] The conductivity, electrochemical window and chemical stability of the solid electrolytes prepared in Examples 1-6 and Comparative Examples 1-3 were tested. The test results are shown in Table 1.

[0118] Table 1

[0119]

[0120]

[0121] Note: The chemical stability after exposure to air for 7 days in Table 1 is obtained by comparing the XRD graph of the solid electrolyte after exposure to air for 0 h with the XRD graph of the solid electrolyte after exposure to air for 7 days; if the XRD graph of the solid electrolyte after exposure to air for 7 days has no obvious change compared with the XRD graph of the solid electrolyte after exposure to air for 0 h, the chemical stability after exposure to air for 7 days is determined to be stable; if a new peak appears in the XRD graph of the solid electrolyte after exposure to air for 7 days compared with the XRD graph of the solid electrolyte after exposure to air for 0 h, the chemical stability after exposure to air for 7 days is determined to be unstable.

[0122] It can be seen from Table 1 that the solid electrolytes provided in Examples 1-6 of the present application have excellent electrical conductivity, a wide electrochemical window and excellent air stability; while the electrical conductivity, electrochemical window and air stability of the solid electrolytes provided in Comparative Examples 1-3 are all poor.

[0123] By comparing Example 1 with Comparative Example 1, it can be seen that the Li4B6O9S2 solid electrolyte prepared in Example 1 has higher electrical conductivity, wider electrochemical window and better air stability than the Li4OBr2 prepared in Comparative Example 1, indicating that when the atomic selection and atomic ratio in the solid electrolyte conform to the general chemical formula defined in the present application, the electrical conductivity, voltage stability and chemical stability of the solid electrolyte can be significantly improved.

[0124] By comparing Example 1 with Comparative Examples 2-3, it can be seen that the synthesis pressure and temperature have an impact on the electrical conductivity, voltage stability and chemical stability of the solid electrolyte, indicating that the synthesis pressure and synthesis temperature specified in the present application can significantly improve the electrical conductivity, voltage stability and chemical stability of the solid electrolyte.

[0125] In summary, the solid electrolyte provided in the present application can have high electrical conductivity, voltage stability and chemical stability, and has good application prospects in all-solid-state batteries.

[0126] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a solid electrolyte, characterized in that: The method comprises synthesizing the formed raw materials; the synthesis pressure is 0.1-30GPa, and the synthesis temperature is 500-3000°C; The chemical formula of the solid electrolyte is Li x B y O z S w , where 0 <x≤4,0<y≤7,0<z≤11,0<w≤2; The raw materials include a lithium source, a boron source, a sulfur source and an oxygen source; The lithium source includes at least one of lithium oxide, lithium peroxide and lithium sulfide, the boron source includes at least one of boron powder, boron oxide and boron sulfide, the sulfur source includes at least one of sulfur powder, lithium sulfide and boron sulfide, and the oxygen source includes at least one of lithium oxide and boron oxide.

2. The method for preparing a solid electrolyte according to claim 1, characterized in that: The synthesis pressure is 3-5 GPa, and the synthesis temperature is 800-1000°C.

3. The method for preparing a solid electrolyte according to claim 1, characterized in that: The synthesis time is 1-100 min.

4. The method for preparing a solid electrolyte according to claim 1, characterized in that: Before synthesizing the formed raw materials, the raw materials are also subjected to ball milling mixing; the ball-to-material ratio of the ball milling mixing is (5-20):1, and the rotation speed of the ball milling mixing is 100-500r / min.

5. The method for preparing a solid electrolyte according to claim 4, characterized in that: The ball milling mixing time is 3-10 hours.

6. The method for preparing a solid electrolyte according to claim 1, characterized in that: The step of preparing the formed raw material comprises: pre-pressing the raw material at 1-30 MPa for 1-20 min.

7. The method for preparing a solid electrolyte according to any one of claims 1 to 6, characterized in that: The synthetic device is selected from any one of a two-sided press, a four-sided press and a hinged six-sided press.

8. A solid electrolyte, characterized in that The solid electrolyte is prepared by the method for preparing a solid electrolyte according to any one of claims 1 to 7.

9. Use of the solid electrolyte as claimed in claim 8 in the preparation of an all-solid-state battery.

Citation Information

Patent Citations

  • Lithium ion-conductive solid electrolyte, method for producing same, solid electrolyte for lithium secondary battery using such solid electrolyte, and all-solid lithium battery using such solid electr

    CN101103486A

  • Solid electrolyte material, preparation method thereof, solid electrolyte sheet and all-solid-state battery

    CN113299979A